COMPARISON OF PERCUTANEOUS VS. LAPAROSCOPIC DRAINAGE FOR RUPTURED LIVER ABSCESS: A RETROSPECTIVE COHORT ANALYSIS - Khuntia, Pradipta Kishore; Mohanty, Sudhansu Sekhar; Hota, Debendra Kumar (Student's Journal of Health Research Africa, 2024)
Background Ruptured liver abscesses pose a significant clinical challenge due to their potential for severe complications, including peritonitis and sepsis. The study compares the outcomes of percutaneous drainage versus laparoscopic drainage for patients with ruptured liver abscesses. Methods Two groups of patients were developed: one for percutaneous drainage (n = 60) and another for laparoscopic drainage (n = 60). Analyses were conducted on baseline variables, procedural outcomes, complication rates, and clinical outcomes. The statistical analysis was done with SPSS 23.0. Results Middle-aged adults dominated the percutaneous and laparoscopic groups, with mean ages of 54.2 and 52.7 years, respectively. Men dominated both groups, with 63.3% of percutaneous and 60% of laparoscopic patients. Percutaneous drainage was associated with a significantly shorter procedure duration (45.3 ± 12.5 minutes vs. 73.8 ± 15.7 minutes, p < 0.001) and lower complication rate (13.3% vs. 30.0%, p = 0.03) compared to laparoscopic drainage. Additionally, patients in the percutaneous group experienced shorter hospital stays (7.2 ± 2.5 days vs. 10.3 ± 3.1 days, p < 0.001) and faster resolution of symptoms (5.1 ± 1.8 days vs. 7.8 ± 2.2 days, p < 0.001). There was no significant difference in the mortality rate between the two groups (3.3% vs. 5.0%, p = 0.56). Conclusion Percutaneous drainage demonstrates advantages over laparoscopic drainage in terms of shorter procedure duration, lower complication rates, and faster recovery for patients with ruptured liver abscesses. However, the slightly higher initial success rate of laparoscopic drainage suggests that both methods are viable, with the choice of procedure depending on individual patient factors and clinical judgment. Recommendations Future prospective studies are needed to validate these findings and explore long-term outcomes associated with each drainage method. Clinicians should consider patient-specific factors when selecting the appropriate drainage technique for ruptured liver abscesses.